Transmembrane 4 L Six Family Member 1 Suppresses Hormone Receptor-–Positive, HER2-Negative Breast Cancer Cell Proliferation - Chen, Jie; Zhu, Jin; Xu, Shuai-Jun; Zhou, Jun; Ding, Xiao-Fei; Liang, Yong; Chen, Guang; Lu, Hong-Sheng (Frontiers in Pharmacology, 2022)
Background: The prognosis of breast cancer varies according to the molecular subtype. Transmembrane 4 L six family 1 (TM4SF1) exhibits different expression patterns among the molecular subtypes of breast cancer. However, the expression profile of TM4SF1 in hormone receptor HR+HER2- breast cancer remains unclear. Methods: TM4SF1 mRNA levels were examined in major subclasses of breast cancer by analyzing The Cancer Genome Atlas (TCGA) datasets. In addition, TM4SF1 protein and mRNA levels in HR+HER2- breast cancer tissue samples were determined by immunohistochemistry and Western blot assay. The effect of TM4SF1 on cell proliferation was evaluated using MTT, colony formation, 3D organoid, and xenograft models, following the TM4SF1 overexpression or knockdown. Results: TCGA database analysis demonstrated that TM4SF1 was downregulated in breast cancer compared with the healthy adjacent breast tissue. In addition, the expression of TM4SF1 in basal-like one and the mesenchymal TNBC tissue was higher than that of the healthy adjacent breast tissue. Other types, including the luminal androgen receptor–positive TNBC tissue, expressed lower levels of TM4SF1. Immunohistochemistry and real-time quantitative PCR assays demonstrated that the TM4SF1 protein and mRNA levels were downregulated in the HR+HER2- breast cancer tissue compared with the healthy adjacent tissue. Moreover, the TM4SF1 overexpression reduced the viability of MCF-7 and ZR-75-1 breast cancer cells, whilst reducing the number of colonies and 3D-organoids formed by these cell lines. By contrast, TM4SF1 knockdown led to an increased MCF-7 cell proliferation. However, in the TNBC cell line, MDA-MB-231, TM4SF1 silencing reduced cell proliferation. In vivo, the TM4SF1 overexpression inhibited MCF-7 xenograft growth in a nude mouse model, which was associated with the downregulation of the Ki-67 expression, apoptosis induction, and inhibition of the mTOR pathway. Conclusion: TM4SF1 is downregulated in HR + HER2-breast cancer, and the overexpression of TM4SF1 suppresses cell proliferation in this cancer subtype.